The VAD Scheme versus Thalidomide plus VAD for Reduction of Vascular Endothelial Growth Factor in Multiple Myeloma: A Meta-Analysis. (11th November 2018) - He, Gan-Lin; Xu, Duo-Rong; Zou, Wai-Yi; He, Sui-Zhi; Li, Juan
Abstract : The VAD (vincristine-doxorubicin-dexamethasone) regimen has been used for decades to treat multiple myeloma (MM). Based on reports that vascular endothelial growth factor- (VEGF-) mediated angiogenesis is critical for MM pathogenesis, the antiangiogenic compound thalidomide has been added to VAD (T-VAD). However, it remains unclear whether T-VAD is more efficacious than VAD for serum VEGF reduction or if the difference influences clinical outcome. Pubmed, Cochrane library, China Biomedical Literature (CBM) database, China National Knowledge Infrastructure (CNKI) database, Vip database, and Wanfang database were searched for relevant studies published up to June 2017. RevMan5.2 was used for methodological quality evaluation and data extraction. Thirteen trials (five randomized, seven nonrandomized, and one historically controlled) involving 815 cases were included. Serum VEGF was significantly higher in MM cases than non-MM controls (MD=353.01, [95%CI 187.52–518.51], P<0.01), and the overall efficacy of T-VAD was higher than that of VAD (RR=1.36, [1.21–1.53], P <0.01). Further, T-VAD reduced VEGF to a greater extent than VAD does ([MD=-49.85, [-66.28− -33.42], P<0.01). The T-VAD regimen also reduced VEGF to a greater extent in newly diagnosed MM patients than it did in recurrent patients ([MD=-120.20, [-164.60–-39.80], P<0.01). There was no significant difference in VEGF between T-VAD patients (2 courses) and nontumor controls (MD=175.94, [-26.08–377.95], P=0.09). Greater serum VEGF reduction may be responsible for the superior efficacy of T-VAD compared to VAD.